2019
DOI: 10.1038/s41571-019-0204-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell-state dynamics and therapeutic resistance in melanoma from the perspective of MITF and IFNγ pathways

Abstract: Targeted therapy and immunotherapy have greatly improved the prognosis of patients with metastatic melanoma, but resistance to these therapeutic modalities limits the percentage of patients with long-lasting responses. Accumulating evidence indicates that a persisting subpopulation of melanoma cells contributes to resistance to targeted therapy or immunotherapy, even in patients who initially have a therapeutic response; however, the root mechanism of resistance remains elusive. To address this problem, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 240 publications
(288 reference statements)
4
77
0
Order By: Relevance
“…In a recent review (Bai et al 2019), it has been proposed that the majority of cells within a melanoma tumor will exist in a continuous spectrum of states rather than fit any specific category and that the outliers will be the most unstable and therefore more likely to revert back to the most common state shared by the majority of cells. However, we feel it more likely that distinct melanoma phenotypes, once established, may become stabilized by positive feedback loops that then are fixed by epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review (Bai et al 2019), it has been proposed that the majority of cells within a melanoma tumor will exist in a continuous spectrum of states rather than fit any specific category and that the outliers will be the most unstable and therefore more likely to revert back to the most common state shared by the majority of cells. However, we feel it more likely that distinct melanoma phenotypes, once established, may become stabilized by positive feedback loops that then are fixed by epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the MITF low cells are dedifferentiated, invasive, and apoptosis-resistant [6][7][8], which gives them the ability to survive harsh conditions, such as under targeted and/or immunotherapy agents [5]. Given the fact that melanomas, under harsh conditions, can become enriched in MITF low cells and that these are more capable of escaping T-cell recognition, loss of MITF may be a mechanism for tumor cells to evade the immune system [9]. Moreover, immune evasion mechanisms are activated either by oncogenic gain-of-function, such as CTNNB1 (which encodes for the protein beta-catenin), or loss-of-function of tumor suppressor genes, such as PTEN [10].…”
Section: Introductionmentioning
confidence: 99%
“…These results thus suggest that Par3 promotes epidermal melanocyte pigmentation and differentiation through steering of MITF function. Considering the emerging albeit controversial roles of MITF in melanoma formation, progression and therapeutic resistance [4,69,70], our findings also raise new questions about the relevance of Par3/MITF signaling in modulating melanoma plasticity.…”
Section: Par3 Acts Upstream Of Mitf Signaling To Promote Melanin Syntmentioning
confidence: 82%